Music as Refuge: Stillness in Brian Cherney’s Mature Piano Works - Di Castri, Zosha (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
“Lingering in the autumnal countryside, all that magic of the ancient forests invincibly came back to me. A gentle, persuasive voice that lulled one into perfect oblivion … and the hollow tones of the angelus, which tolled the fields to sleep.” For Cherney, this Debussy quotation is one of the most evocative descriptions of stillness and closely tied to his own childhood memories—a perfect fusion of mood, landscape, and near silence. Having grown up studying piano, Cherney uses the instrument as a personal outlet, a compositional tool, and a means for auditioning the sounds of his imagination. Through the study of Debussy’s revolutionary music, Cherney came to his mature style in the late 1970s. Using Dans le crépuscule du souvenir … , In the Stillness of the Seventh Autumn, and Tombeau as case studies, this article uses biographical, analytical, and aesthetic perspectives to examine Cherney’s dual approach to stillness: as a space for inspiration and one for withdrawal.